2018
DOI: 10.1111/cts.12542
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Genetic Variation Associated with Tamoxifen Biotransformation in American Indian and Alaska Native People

Abstract: Despite evidence that pharmacogenetics can improve tamoxifen pharmacotherapy, there are few studies with American Indian and Alaska Native (AIAN) people. We examined variation in cytochrome P450 (CYP) genes (CYP2D6, CYP3A4, CYP3A5, and CYP2C9) and tamoxifen biotransformation in AIAN patients with breast cancer (n = 42) from the Southcentral Foundation in Alaska and the Confederated Salish and Kootenai Tribes in Montana. We tested for associations between CYP diplotypes and plasma concentrations of tamoxifen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
0
34
0
5
Order By: Relevance
“…15 The CYP2D6 polymorphisms were evaluated in an American Indian and Alaska Native population in a convenience sample of 380 subjects from the Southcentral Foundation and other 187 subjects from the University of Montana and of the Confederated Salish and Kootenai Tribes. 21 This cohort study showed that CYP2D6 Ã 1 (45.21%) and CYP2D6 Ã 2 (26.6%) were the most common alleles identified in the Southcentral Foundation population.…”
Section: Ethnic Characteristics Of Cyp2d6 Allelesmentioning
confidence: 83%
See 2 more Smart Citations
“…15 The CYP2D6 polymorphisms were evaluated in an American Indian and Alaska Native population in a convenience sample of 380 subjects from the Southcentral Foundation and other 187 subjects from the University of Montana and of the Confederated Salish and Kootenai Tribes. 21 This cohort study showed that CYP2D6 Ã 1 (45.21%) and CYP2D6 Ã 2 (26.6%) were the most common alleles identified in the Southcentral Foundation population.…”
Section: Ethnic Characteristics Of Cyp2d6 Allelesmentioning
confidence: 83%
“…The CYP2D6 gene was the major contributor to significant associations between genetic variation and TMX metabolism. 21,27,29 The CYP2D6 variation was significantly associated with plasma endoxifen (p ¼ 0.0010) levels and with the endoxifen/TMX metabolic ratio (p ¼ 4.4 Â 10 À7 ), particularly CYP2D6 Ã 5 and CYP2D6 Ã 10. 21,29 Caucasian patients carrying the CYP2D6 Ã 4 allele had a significantly increased risk of recurrence of breast cancer.…”
Section: Cyp2d6 Polymorphisms and Tamoxifen Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Given these community-defined goals, we were the first to evaluate tamoxifen pharmacogenetics in AIAN women and found that women who are cytochrome P450 2D6 poor metabolizers are at an increased risk of having subtherapeutic concentrations of endoxifen, the active metabolite of tamoxifen, and may be at risk for cancer recurrence. 3 Our approach allowed us to identify genetic variation affecting cancer treatment in AIAN communities and to contribute to general scientific knowledge by informing tamoxifen pharmacogenetics globally. These early pharmacogenomics research studies have evolved to include gene-environment interactions and qualitative assessments of the acceptability of pharmacogenetic testing as trust and interest in research have grown in the community.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, genetic research in ANAI communities must address areas of known disparities, clearly delineate potential health benefits and risks, and provide adequate protections against individual and group harm [11,12]. ANAI communities expect transparent research practices that include tribal oversight and approval of the research, a robust informed consent process, and dissemination of study updates and findings throughout the research project [13][14][15][16][17]. Research partnerships that have taken the time to meet these expectations resulted in equitable partnerships with novel genetic findings [14,16,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%